To simplify the polynomial expression \((r - 1)(r^2 - 2r + 3)\), we will use the distributive property (also known as the FOIL method).
-
Distribute \(r\) in \((r - 1)\):
- \(r \cdot r^2 = r^3\)
- \(r \cdot (-2r) = -2r^2\)
- \(r \cdot 3 = 3r\)
So we get: \[ r(r^2 - 2r + 3) = r^3 - 2r^2 + 3r \]
-
Distribute \(-1\) in \((r - 1)\):
- \(-1 \cdot r^2 = -r^2\)
- \(-1 \cdot (-2r) = 2r\)
- \(-1 \cdot 3 = -3\)
So we get: \[ -1(r^2 - 2r + 3) = -r^2 + 2r - 3 \]
-
Now combine all the terms from both distributions: \[ r^3 - 2r^2 + 3r - r^2 + 2r - 3 \]
-
Combine like terms:
- \(r^3\)
- \(-2r^2 - r^2 = -3r^2\)
- \(3r + 2r = 5r\)
- And \(-3\)
Thus, the simplified polynomial is: \[ r^3 - 3r^2 + 5r - 3 \]
So, in the format requested: ___r^3 + ___r^2 + ___r + ___
You would fill it in as: 1 \(r^3\), -3 \(r^2\), 5 \(r\), -3.